Colorectal endoscopic submucosal dissection in the USA: The current state and future perspectives - Abdulrahman Qatomah; Hiroyuki Aihara (DEN Open)
Abstract Endoscopic submucosal dissection (ESD) is a transformative advancement in the endoscopic management of superficial gastrointestinal lesions. Initially conceived for the treatment of early gastric cancer, ESD has demonstrated proficiency in achieving en‐bloc resection of superficial gastrointestinal lesions. ESD has experienced widespread acceptance in Japan and East Asia; however, its adoption in the USA remains delayed. This initial hesitancy could be attributed to procedural complexity and training demands; nonetheless, recently, ESD has been gaining popularity in the USA. This is due to the advancements in endoscopic technology, tailored training programs, and cumulative evidence regarding the efficacy and safety of ESDs. This review aimed to deliberate the historical progress, current implementation, and prospective trajectory of ESDs in the USA. With ongoing clinical research, technological integration, and educational efforts, ESD is likely to become the gold standard for managing large gastrointesitinal lesions. This progress marks an imperative step toward less invasive, more precise, and patient‐centric approaches regarding advanced therapeutic endoscopy in the USA.